Bone morphogenetic proteins: The anomalous molecules - Aena Pundir Jain (Journal of Indian Society of Periodontology, 2013)
Bone is unique of all the tissues in the vertebrate organism. When injured, it heals by formation of new bone. Bone morphogenetic proteins (BMPs) are powerful inductors of the osteogenic activity during the embryologic bone formation phase and in cases of bone healing. They have proliferative effects on different cellular types, showing chemotactic properties and are able to induce mesenchymal cells differentiation into osteoblastic and chondroblastic line cells. Both primary cells and cell lines have been shown to respond to BMPs. Further the ability of embryonic cells to respond to BMPs by differentiating into cartilage and bone cells suggests that they are involved in the development of embryonic skeletal system. In addition, these proteins can also promote the angiogenesis, regulate the activity of some growth factors, and affect the production of these growth factors, which is helpful for the osteogenesis. BMPs have been considered as the most potent growth factors that can promote the bone regeneration. Thus, the aim of this review is to emphasize on the unique nature of the BMP molecules regarding their structure, classification, signaling mechanism, etc., as BMPs are the only molecules which show such deviation from the normal order, type. This will further help in understanding the role of BMPs and their potential advances which are necessary to facilitate the process of regeneration in periodontics.